STUDI KOMPARATIF PANDANGAN TOLERANSI BERAGAMA BERDASARKAN RUMPUN KEILMUAN DI UNIVERSITAS GADJAH MADA - Permana, Adhitya Rangga; Levina, Vincentia Seane; Lismiramdani, Firsiyanda; Amaldo, Rizky Iskar; Hasyidan A. A., Ghamdan Ghazi; Adyatma, Ilham Rakha (Balai Diklat Keagamaan Jakarta, 2025)
This study investigates the comparative perspectives on religious tolerance among students from different academic disciplines—Social-Humanities (Soshum) and Science-Technology (Saintek)—at Universitas Gadjah Mada. Using a quantitative comparative method, data were collected via an online questionnaire using a five-point Likert scale. The study involved 60 purposively selected respondents from both clusters. Results from the Shapiro-Wilk test indicated non-normal distribution in both groups, prompting the use of the Mann-Whitney U test. Although descriptive data showed that Soshum students tended to have higher and more consistent tolerance scores, the inferential analysis found no statistically significant difference between the two groups (p = 0.279). Visual data further indicated a broader variation in Saintek students' tolerance levels. The findings suggest that while disciplinary background may influence perspectives, the multicultural campus environment acts as a moderating factor. Theoretical frameworks of objective conservative and subjective liberal tolerance supported these interpretations. The study recommends cross-disciplinary character education programs to foster inclusive attitudes in higher education. Abstrak Penelitian ini mengkaji perbandingan pandangan mengenai toleransi beragama di kalangan mahasiswa dari rumpun keilmuan Sosial-Humaniora (Soshum) dan Sains-Teknologi (Saintek) di Universitas Gadjah Mada. Dengan pendekatan kuantitatif komparatif, data dikumpulkan melalui kuesioner daring menggunakan skala Likert lima poin. Sebanyak 60 responden dipilih secara purposif dari masing-masing rumpun. Hasil uji Shapiro-Wilk menunjukkan bahwa data tidak terdistribusi normal, sehingga analisis menggunakan uji Mann-Whitney U. Meskipun data deskriptif memperlihatkan mahasiswa rumpun Soshum memiliki skor toleransi yang lebih tinggi dan konsisten, analisis inferensial menjelaskan tidak terdapat perbedaan signifikan secara statistik antara kedua rumpun (p = 0,279). Visualisasi data mengungkapkan variasi yang lebih besar dalam tingkat toleransi pada mahasiswa rumpun Saintek. Temuan ini mengindikasikan bahwa latar belakang keilmuan mempengaruhi sudut pandang, namun lingkungan kampus yang multikultural turut berperan sebagai faktor moderasi. Kerangka teori toleransi konservatif objektif dan liberal subjektif mendukung interpretasi temuan. Hasil studi merekomendasikan program pendidikan karakter lintas disiplin untuk menumbuhkan sikap inklusif di lingkungan pendidikan tinggi.